Reduction in Perinatal Mortality after Implementation of HBB Training at a District Hospital in Mali. (19th October 2019) - Innerdal, M; Simaga, I; Diall, H; Eielsen, M; Niermeyer, S; Eielsen, O; Saugstad, O D
Abstract: Background: Mali has a high neonatal mortality rate of 38/1000 live births; in addition the fresh stillbirth rate (FSR) is 23/1000 births and of these one-third are caused by intrapartum events. Objectives: The aims are to evaluate the effect of helping babies breathe (HBB) on mortality rate at a district hospital in Kati district, Mali. Methods: HBB first edition was implemented in April 2016. One year later the birth attendants were trained in HBB second edition and started frequent repetition training. This is a before and after study comparing the perinatal mortality during the period before HBB training with the period after HBB training, the period after HBB first edition and the period after HBB second edition. Perinatal mortality is defined as FSR plus neonatal deaths in the first 24 h of life. Results: There was a significant reduction in perinatal mortality rate (PMR) between the period before and after HBB training, from 21.7/1000 births to 6.0/1000 live births; RR 0.27, (95% CI 0.19–0.41; p < 0.0001). Very early neonatal mortality rate (24 h) decreased significantly from 6.3/1000 to 0.8/1000 live births; RR 0.12 (95% CI 0.05–0.33; p = 0.0006). FSR decreased from 15.7/1000 to 5.3/1000, RR 0.33 (95% CI 0.22–0.52; p < 0.0001). No further reduction occurred after introducing the HBB second edition. Conclusion: HBB may be effective in a local first-level referral hospital in Mali.